OD REFLEKSJI DO KONSTRUOWANIA WIEDZY I WSPÓLNOTY KOMUNIKACYJNEJ: WYNIKI BADANIA W DZIAŁANIU - Piegzik, Wioletta (Neofilolog, 2019)
The purpose of the following paper is to consider the development of reflection in foreign language learners. Based on the results of action research, we show to what extent the performance of group tasks affected the perception of reality and influenced changes in the communication and learning behavior of participants of an action research project. Reflection is analyzed on the basis of statements contained in student diaries and transcriptions from video recording of discussions. This means that on the one hand, we are interested in the opinions, conclusions and evaluations made by learners, but on the other hand, we attach importance to the coherence between formulated judgments and practical group action. It is not uncommon that declarations are not in accordance with the activities undertaken and that, in consequence, their value is questionable. The paper also points to difficulties associated with becoming a reflective person as well as the restrictions connected with the scientific measurements of this process.